(untitled) (Journal of Environmental Microbiology and Toxicology, 2020)
COVID-19 is caused by the coronavirus SARS-CoV-2 which shares genetic similarity to the agent for the SARS virus (SARS-CoV). The growth of these two viruses in Vero E6 cells shows sigmoidicity and hence various primary growth models can be applied to extract useful growth parameters. The overlapping of the 95% confidence intervals for the parameters A (lower asymptote value of virus titer) and ïm (maximum specific viral titer) in the modified Logistics model indicates no significant differences between these two parameters. However, the ymax or viral titer log (PFU/mL) upper asymptote values did not overlap suggesting significant differences between the two values with viral titer values for SARS-CoV (SARS) value higher than SARS-CoV-2 (COVID-19). The result obtained in this study warrants further study to the infection rate for both viruses that can be useful in studying potential similarity and differences between the two viruses.